Hubungan Kebiasaan Sarapan dan Aktivitas Fisik dengan Kejadian Anemia pada Remaja Putri Kelas X di SMA Negeri 3 Cilacap: Correlation of Breakfast Habits and Physical Activity with the Incidence of Anemia in Grade X Female Adolescents at SMA Negeri 3 Cilacap - Siti Shohifaturrohmaniyah; Diah Atmarina Yuliani (Jurnal Kebidanan Harapan Ibu Pekalongan, 2025)
Anemia is problem health serious global society one of them attack teenager princess and woman who are menstruation. WHO estimates teenager It is estimated that 30% of women worldwide suffer from anemia in 2024. Prevalence Anemia in adolescents worldwide in 2019 was 15%, namely in developing countries by 27% and in developed countries by 6%. Prevalence anemia in adolescents daughter based on Basic Health Research 2018 shows that prevalence anemia in adolescents by 32%, meaning 3-4 out of 10 teenagers suffer anemia or lack cell blood red Percentage teenager daughter grades 7 and 10 in Indonesia who were screened for Hb in 2023 were 85.39%, with results 30.45% experienced anemia while in the Regency Cilacap teenager the princess who did screening in 2024 it will reach 92.2% with results 39.05% experienced anemia. Activity physique can to smoothen system metabolism substance nutrition in body. Research objectives for know connection habit breakfast and activities physique with incident anemia in adolescents daughter class X at State Senior High School 3 Cilacap. Research Design cross-sectional accidental sampling 93 respondents students of State Senior High School 3 Cilacap. Data analyzed in a way univariate and bivariate using the Spearman rank test. The results of the study show habit breakfast category good 90.3%, activity physique part big category moderate 58.1%, many no experience anemia 48.4%. There are two, namely, the relationship significant and enough between habit breakfast with incident anemia in adolescents daughter class X at State Senior High School 3 Cilacap in 2025 (pv = 0.001 < 0.05) and the relationship significant and enough between activity physique with incident anemia in adolescents daughter class X at State Senior High School 3 Cilacap 2025 (pv = 0.001 < 0.05).